Fe(Se, Te) coated conductors deposited on simple rolling-assisted biaxially textured substrate templates. (15th July 2019) - Sylva, G; Augieri, A; Mancini, A; Rufoloni, A; Vannozzi, A; Celentano, G; Bellingeri, E; Ferdeghini, C; Putti, M; Braccini, V
Abstract: In this paper we study the feasibility of Fe(Se, Te) coated conductors on a simple rolling-assisted biaxially textured substrate (RABiTS) template. Starting from commercially available Ni–5 at% W tapes which show an out-of-plane orientation of about 7° and an in-plane orientation around 5°, we realized a RABiTS template for Fe(Se, Te) coated conductor fabrication by depositing CeO2 thin films on the metallic tape. The oxide buffer layers, deposited via pulsed laser ablation, exhibit an out-of-plane and an in-plane orientation suitable for Fe(Se, Te) deposition and act as a chemical barrier against Ni diffusion. Fe(Se, Te) thin films deposited on such a simple template show a superconducting transition at 16 K and very high upper critical field values with a Δ T c, 0 of only 3 K in 18 T. The transport critical current reaches values of 1.7 × 10 5 A cm −2 at 4.2 K in self-field and is reduced by less than one order of magnitude up to 18 T, remaining isotropic with respect to the magnetic field direction.